Isolated intraocular relapses of primary cerebral lymphomas: An LOC network study. Issue 5 (14th July 2022) - Younan, Nadia; Soussain, Carole; Choquet, Sylvain; Cassoux, Nathalie; Touitou, Valérie; Schmitt, Anna; Chinot, Olivier; Oberic, Lucie; Damaj, Gandhi; Houot, Roch; Ghesquières, Hervé; Laribi, Kamel; et al.
Abstract: Most relapses of primary central nervous system lymphoma (PCNSL) occur in the brain and are associated with a poor prognosis. Isolated intraocular relapses (IIORs) are rare and poorly described. We retrospectively selected from the French Lymphome Oculo‐Cérébral database PCNSL patients who initially presented with cerebral localization and who experienced IIOR during the course of the disease. Of the 1472 patients included in the database, 55 patients presented an IIOR. Their median age was 68 years, and median Karnofsky Performance Status 80. IL‐10 levels in the aqueous humor and/or in the vitreous were increased in 42/46 patients. 45/55 patients received systemic chemotherapy, and 11/55 received high‐dose chemotherapy with autologous stem cell transplantation (HCT‐ASCT) as consolidation treatment. After a median follow‐up of 69 months, 42/55 patients had relapsed, including 90% of the patients who did not receive HCT‐ASCT at IIOR and 40% of the patients who received HCT‐ASCT at IIOR ( p < 0.001). The first relapse after the initial IIOR was exclusively in the eye in 23/42 patients, and 29/42 patients had a subsequent brain relapse during the course of the disease. The median progression‐free survival, brain‐free survival and overall survival from IIOR were 12.2, 48.6 and 57.1 months, respectively. Isolated intraocular relapse is not exceptional in the course of PCNSL and deserves systematic ophthalmological follow‐up. Its prognosis is much better than the prognosis of brain relapse, with an evolution close to that of primary vitreoretinal lymphoma. With the exception of patients who received HCT‐ASCT at IIOR, almost all patients subsequently relapsed, often with other IIORs.